An overview of the problematic issues in logistics cost management - Muha, Robert (Array, 2019)
Logistics cost management is associated with certain specific challenges, since increasing the quality of logistics services for customers often comes with increased logistics costs. In addition, reducing the costs of one logistic component causes an increase in the costs of another logistic component, which results in higher total logistics costs. Various cost models have been developed to support the optimisation of logistics activities, which represent the main focus of research and a key practical tool for logistics management. The purpose of the study is therefore to determine whether current scientific studies are addressing the issues related to logistics cost management. The aim of the study is to determine the scope of the optimisation of individual logistics models from the point of view of how individual logistics costs categories and processes are treated. The analysis of logistics costs management issues provides an important empirical foundation for the improvement of logistic processes in supply chains and synthesises scientific literature in the field of logistics cost modelling, which represents an important framework for future empirical studies.